Discrete-time sliding mode control of linear systems with input saturation - Veselić, Boban; Milosavljevič, Čedomir; Peruničić-Draženović, Bronislava; Huseinbegović, Senad; Petronijević, Milutin (Zielona Góra: Uniwersytet Zielonogórski)
of the fast response without overshoot and strong robustness to matched disturbances. The system input saturation is imposed during the design due to inevitable limitations of most actuators. The system disturbances are compensated by employing nonlinear estimation by integrating the signum of the sliding variable. Hence, the proposed control structure may be regarded as a super-twisting-like algorithm. The designed system stability is analyzed as well as the sliding manifold convergence conditions are derived using a discrete-time model of the system in the [delta]-domain. The results obtained theoretically have been verified by computer simulations.
Keywords: discrete-time sliding mode control; super-twisting controller; input saturation; disturbance compensation